The Need Analysis of Online Placement Test for Teaching Indonesian to Speakers of Other Languages (BIPA) - Septyara Lingce; Syahrial Syahrial; Wisma Yunita (IAIN Bengkulu, 2022)
This research aimed to investigate the need for online placement tests for Teaching Indonesian to Speakers of Other Languages (BIPA) at Bengkulu University. This research used a descriptive qualitative approach and the method was a semi-structured interview. Three international students from Cambodia were interviewed in different Zoom video call sessions during this research. The data collected were then analyzed by using the content analysis technique. There are some findings in this research. First, there was no placement test for BIPA students at Bengkulu University. Second, according to the existing condition of the students, they had different reasons, exposures, experiences, and frequencies in learning or using Indonesian language. Third, the students could not do written tests or paper-based tests (PBT) that required them to come to the test venue in Bengkulu University during the pandemic situation, so an online placement test was used as an alternative. Moreover, the students had some topic preferences to be learned and discussed in Indonesian language. These findings revealed that an online placement test is needed to find out the students’ abilities and to place the students into appropriate levels before conducting BIPA course at Bengkulu University. In the end, the result of this research can later be used to compile placement test materials in accordance with the needs of BIPA students.